THE ROLE OF HADITH IN DEVELOPING ETHICAL STANDARDS IN ISLAMIC LAW - Sajida Faraz; Prof. Dr. Tahir Hameed Ullah Khan; Ayesha Muhammad Tahir Iqbal Mufti (Journal of Religion and Society, 2024)
After the Quran, the second primary source of Islamic law is Hadith, or reports that contain the words, deeds, and tacit endorsements of Prophet Muhammad (PBUH). In order to establish the basis of Islamic jurisprudence (fiqh), this study investigates the Hadith's relevance to the formation of moral standards. The ethical precepts of Islamic law, such as justice (adl), kindness (rahmah), and honesty (sidq), are derived not just from the teachings of the Quran but also from the Hadith literature, which provides significant background and reinforcement. Since issues differ depending on the fields, such as social justice, business ethics, interpersonal relationships, and environmental concerns, the Prophet Muhammad's (PBUH) principle application in daily life—which is subsequently documented in Hadiths—remains true when discussing the universal framework within which ethical dilemmas are dynamic. In order to determine how the prophetic tradition itself addresses pertinent universal ethical issues and offers solutions to those issues that are pertinent now, this study examines a few chosen Hadiths. It also looks at both traditional and contemporary approaches to using Hadith to derive moral principles. It emphasizes the need for flexibility in handling freshly developing ethical issues by striking a balance between textual adherence and contextual comprehension. The ways the Hadith are misused and misinterpreted are critically examined, leading to ethical aberrations that highlight the necessity of a strong scholarly approach to their application and verification. The findings demonstrate the Hadith's crucial role in the larger ethical framework that upholds social justice, equity, and peace. A fuller comprehension of Islam's contributions to universal ethical discourses is fostered by this research, which revisits the ethical ideas drawn from Hadith and urges their application to current global concerns. Keywords: Hadith, Islamic Law, Ethics, Fiqh, Justice, Mercy, Prophet Muhammad (PBUH), Ethical Standards, Contemporary Applications, Islamic Jurisprudence